Extending systems thinking in planning and evaluation using group concept mapping and system dynamics to tackle complex problems. (February 2017) - Hassmiller Lich, Kristen; Urban, Jennifer Brown; Frerichs, Leah; Dave, Gaurav
Highlights: Describe the challenges complexity poses to program planning and evaluation. Introduce an approach to systems thinking grounded in system dynamics. Describe the synergy between systems thinking (SD) and group concept mapping. Illustrate how SD could be used to extend GCM in a mental health systems project. Abstract: Group concept mapping (GCM) has been successfully employed in program planning and evaluation for over 25 years. The broader set of systems thinking methodologies (of which GCM is one), have only recently found their way into the field. We present an overview of systems thinking emerging from a system dynamics (SD) perspective, and illustrate the potential synergy between GCM and SD. As with GCM, participatory processes are frequently employed when building SD models; however, it can be challenging to engage a large and diverse group of stakeholders in the iterative cycles of divergent thinking and consensus building required, while maintaining a broad perspective on the issue being studied. GCM provides a compelling resource for overcoming this challenge, by richly engaging a diverse set of stakeholders in broad exploration, structuring, and prioritization. SD provides an opportunity to extend GCM findings by embedding constructs in a testable hypothesis (SD model) describing how system structure and changes in constructs affect outcomes over time. SD can be used to simulate the hypothesized dynamics inherent in GCM concept maps. We illustrate the potential of the marriage of these methodologies in a case study of BECOMING, a federally-funded program aimed at strengthening the cross-sector system of care for youth with severe emotional disturbances.